Characteristics of Oxidative Storage Stability of Canola Fatty Acid Methyl Ester Stabilised with Antioxidants - Prakoso, Tirto; Udomsap, Parncheewa; Tanaka, Akiko; Hirotsu, Toshihiro; Goto, Shinichi (ITB Journal Publisher, LPPM ITB, 2012)
TheÂ storageÂ effectsÂ onÂ theÂ oxidationÂ characteristicsÂ ofÂ fattyÂ acid methyl ester of canola oil (CME) were investigatedÂ in this study.CME stabilised withÂ twoÂ antioxidants, i.e.2,6-di-tert-bytyl-p-cresolÂ (BHT) and 6,6-di-tert-butyl-2, 2â-methylendi-p-cresolÂ (BPH),Â wasÂ stored at 20, 40 andÂ 60Â°C.TheÂ oxidation stability dataÂ were measuredÂ byÂ theÂ Rancimat testÂ method andÂ it wasÂ found Â that both BHT and BPHÂ addition increasedÂ the oxidation resistance ofÂ theÂ CME.Â The results showed that when BPH or BHT was added at a concentration of 100 ppm, the oxidation induction period of the neat CME samples increased from 5.53 h to 6.93Â hand Â 6.14 h,Â respectively.Â Comparing both antioxidants,Â BPHÂ proved to be moreÂ effectiveÂ inÂ increasingÂ theÂ oxidationÂ resistanceÂ whenÂ bothÂ antioxidants were added at the same concentration.Â Furthermore, the oxidation induction timedecreasedÂ linearlyÂ withÂ theÂ storageÂ time.Â ItÂ wasÂ shownÂ thatÂ theÂ oxidation occurredÂ rapidlyÂ inÂ theÂ firstÂ 8Â weeksÂ ofÂ storage.Â Later,Â aÂ kineticÂ studyÂ was undertakenÂ andÂ first-orderÂ kineticsÂ wereÂ appliedÂ toÂ explainÂ theÂ oxidation characteristics ofÂ theÂ CME added with antioxidants. This kinetic study focused onÂ exploitingÂ theÂ activationÂ energyÂ values Â obtainedÂ fromÂ theÂ Arrheniusequations. Also, theÂ oxidation effects onÂ otherÂ quality parameters, including acid value, peroxide value, kinematic viscosity, and water content, were examined.